Selection of a linear combination of common factors as a coincident index for the colombian economy (2019)
The main goal of this work is to propose a general methodology to create a coincident index based on linear combinations of common factors, and to test it on scenarios from simulations and on a case study for the Colombian economy. A whole methodological approach to produce point estimates, confidence regions, and to test hypotheses is presented. Besides, the results for the scenarios show how promising this new proposal is with respect to previous achievements in the scientiﬁc community.